The Macroprudential Framework : Policy Responsiveness and Institutional Arrangements - Lim, Cheng (IMF Working Papers; Working Paper ;, 2013)
This paper gauges if, and how, institutional arrangements are correlated with the use of macroprudential policy instruments. Using data from 39 countries, the paper evaluates policy response time in various types of institutional arrangements for macroprudential policy and finds that the macroprudential framework that gives the central bank an important role is associated with more timely use of macroprudential policy instruments. Policymakers may also tend to use macroprudential instruments more quickly if the ability to conduct monetary policy is somehow constrained. This finding points to the importance of coordination between macroprudential and monetary policy.